(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article investigates the usage of environmental terms in the English language as portrayed in mass media sources. It examines how environmental terminology is employed, represented, and perceived within various forms of media, including news articles, television broadcasts, online platforms, and social media. Through an analysis of linguistic patterns, rhetorical strategies, and discursive frameworks, the article aims to shed light on the role of mass media in shaping public discourse and awareness surrounding environmental issues. By exploring the linguistic nuances and socio-cultural implications of environmental language in the media, this article offers insights into how environmental narratives are constructed, disseminated, and interpreted by diverse audiences.